The Impact of Corporate Social Responsibility on Firm’s Financial Performance - Ahmed, Tanveer; Butt, Babar Zaheer; Majeed, Waleed Khalid (Information Management and Business Review, 2018)
Corporate Social Responsibility (CSR) is now an integral part of business model of most of the modern organizations. Companies are making efforts to play their role in improving society in one or other ways. The scope of efforts ranges from donating money to nonprofit organizations to employing environmental-friendly policies in their workplace. As per the general global perception the corporate sector of Pakistan has been lacking behind in respect of CSR implementation. It has largely concentrated on profit minting rather than taking care of the welfare aspects of employees and other stakeholders. This attitude has affected the business and as a result industry has failed to keep pace with the modern industry. The objective of this study is to analyze the impact of CSR on firm’s financial performance. The research therefore predicates that increase in CSR activities of poor CSR firms shall have a negative effect on the company’s financial performance. Whereas, Middle CSR firms having a positive relationship with Excess Value (EV) will enhance the project performance, financial stature and future prospect of the firms. However, the firms with the best CSR will always have a positive relationship with the firm’s financial performance but its impact will not be observed significantly on the firm’s financial condition.